rozwiąż nierówności......



Rozwiąż Nierówności class=

Odpowiedź :

ZbiorJ

[tex]1+9\cdot (x+1)\cdot (x-1) \geq \dfrac{x-36}{3} +(3x-2)^{2} ~~\mid \cdot 3\\\\3+27(x^{2} -1)\geq x-36 +3\cdot (9x^{2} -12x+4)\\\\3+27x^{2} -27\geq x-36 +27x^{2} -36x+12\\\\3-27\geq x-36 -36x+12\\\\-24\geq -35x-24\\\\35x \geq -24+24\\\\35x \geq 0~~\mid \div 35\\\\x\geq 0~~\Rightarrow ~~x\in <0,+ \infty )\\\\korzystam~~ze~~wzorow~~skroconego~~mnozenia:\\\\(x-y)\cdot (x+y )=x^{2} -y^{2} \\\\(x-y)^{2} =x^{2} -2\cdot x\cdot y + y^{2}[/tex]